(untitled) (Journal of Plant Disease Sciences, 2025)
Wheat is the main cereal crop cultivated by Indian farmers after rice. Many fungal diseases are reported in wheat but brown rust is the most important air borne foliar disease which cause severe losses in wheat production and grain quality worldwide. There are many principles of disease management, among them resistance source is an eco-friendly and effective measure. In this study three hundred wheat genotypes were tested in the field under artificially inoculated condition to calculate their disease reaction, average coefficient of infection and area under disease progress curve. From them thirty two genotypes were showed immune response, twenty four genotypes were found resistance against brown rust pathogen with AUDPC value between 0 to 10. Eighty genotypes showed moderately resistance response with AUDPC value 10 to 100 and seventy seven were observed moderately susceptible reaction with AUDPC 100 to 500. Remaining 87 genotypes recorded to have susceptible reaction withAUDPC value more than 500.